Inter-ministerial Ordinance 284/2018 (Brazil) and new “sociobiodiversity label” incentivize farmers to continue growing and selling local species via institutional procurement and alternative market channels - CGIAR Research Program on Agriculture for Nutrition and Health (2018)
Innovative multi-sectoral policy platforms bring together the environment, agriculture and health sectors. In Brazil, partners mainstreamed nutritious food biodiversity into policies that support smallholder farmer livelihoods, local agriculture, and improved nutrition, with a focus on institutional procurement. New user database on nutritional value of food biodiversity available, open access https://www.bioversityinternational.org/news/detail/healthy-foods-you-havent-heard-of-yet-the-biodiversity-for-food-and-nutrition-database/